Neutrophil–lymphocyte ratio is associated with arterial stiffness in postmenopausal women with osteoporosis. Issue 1 (July 2015) - Yu, Xin-yang; Li, Xue-song; Li, Ying; Liu, Tiemin; Wang, Rui-tao
Highlights Systemic inflammation may be a common mechanism for the development of osteoporosis (OP) and atherosclerosis. Neutrophil/lymphocyte ratio (NLR), an inexpensive marker, is increased in OP. BaPWV, an index of arterial stiffness, is elevated in OP. NLR is independently associated with arterial stiffness in OP.